L-Canavanine and protein synthesis in the tobacco hornworm Manduca sexta. - Rosenthal, G A (1986)
L-Canavanine, a nonprotein amino acid of certain leguminous plants, manifests potent insecticidal properties in a canavanine-sensitive insect such as the tobacco hornworm Manduca sexta (L.) (Sphingidae). This arginine analog is activated and aminoacylated by arginyl-tRNA synthetase and incorporated into nascent polypeptide chains to create structurally aberrant, canavanine-containing proteins. Analysis of incorporation of [3H]leucine into protein in M. sexta larvae that had been injected with canavanine revealed that this arginine analog stimulates protein synthesis. During the first 3 hr after injection of canavanine, canavanine-mediated net stimulation of protein formation was readily discerned. Thereafter, the stimulation of protein synthesis appeared to be offset by the preferential degradation of anomalous proteins. Double-label protein-turnover experiments with larvae injected with [14C]canavanine- and [3H]arginine-containing hemolymph proteins showed that canavanine-containing proteins were degraded preferentially.